From subsistence to exchange and other essays - Bauer, P. T. (Péter Tamás) (Princeton University Press, 2000)
Peter Bauer, a pioneer of development economics, is an incisive thinker whose work continues to influence fields from political science to history to anthropology. As Nobel Laureate Amartya Sen writes in the introduction to this book, "the originality, force, and extensive bearing of his writings have been quite astonishing." This collection of Bauer's essays reveals the full power and range of his thought as well as the central concern that underlies so much of his diverse work: the impact of people's conduct, their cultural institutions, and the policies of their governments on economic prog.
Keywords: Economic development.; Commerce.; Economics.; Commerce; Economics; Développement économique.; Économie politique.; economic development.; economics.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic development; Economische ontwikkeling.; Internationale handel.